Konsep Tawadhu' Dan Relevansinya Dalam Kehidupan Sosial - Khoirul Azmi Harahap; Sardima Al-Fitra; Maryam Dewi Tsaniyah; Edi Hermanto (GLOBAL SCIENTS PUBLISHER, 2026)
Tawadhu' is a noble morality that receives significant attention in the Qur'an because it plays a role in shaping the Muslim personality and creating harmonious social relationships. Amidst technological and social media developments that have the potential to encourage individualism, riya' (showing off), and arrogance, the value of tawadhu' has become increasingly relevant to study. This study aims to analyze the concept of tawadhu' in the Qur'an and examine its relevance in contemporary social life. The study used a library research method with a descriptive qualitative approach. Data sources consisted of the Qur'an as a primary source and scientific books, journal articles, and relevant academic literature as secondary sources. Data were collected through documentation techniques and analyzed descriptively. The results show that tawadhu' is an attitude of humility born from an awareness of the greatness of Allah SWT and human limitations, reflected in behavior that respects others, is open to advice, behaves politely, and avoids arrogance. In social life, tawadhu' serves to build harmony, strengthen solidarity, shape good character, and prevent conflicts arising from selfishness and arrogance. Therefore, the value of humility (tawadhu') has strong relevance in modern social life as a foundation for building a harmonious, inclusive, and civilized society in accordance with the teachings of the Qur'an.